Understanding surgeon decision making in the use of radiotherapy as neoadjuvant treatment in rectal cancer. (December 2015) - Ansari, Nabila; Young, Christopher J.; Schlub, Timothy E.; Dhillon, Haryana M.; Solomon, Michael J.
Abstract: Background: Strong evidence supports the use of neoadjuvant radiotherapy in rectal cancer to improve local control. This randomised controlled trial aimed to determine the effect of clinical and non-clinical factors on decision making by colorectal surgeons in patients with rectal cancer. Methods: Two surveys comprising vignettes of alternating short (4) and long (12) cues identified previously as important in rectal cancer, were randomly assigned to all members of the CSSANZ. Respondents chose from three possible treatments: long course chemoradiotherapy (LC), short course radiotherapy (SC) or surgery alone to investigate the effects on surgeon decision and confidence in decisions. Choice data were analysed using multinomial logistic regression models. Results: 106 of 165 (64%) surgeons responded. LC was the preferred treatment choice in 73% of vignettes. Surgeons were more likely to recommend LC over SC (OR 1.79) or surgery alone (OR 1.99) when presented with the shorter, four-cue scenarios. There was no significant difference in confidence in decisions made when surgeons were presented with long cue vignettes (P = 0.57). Significant effects on the choice between LC, SC and surgery alone were tumour stage (P < 0.001), nodal status (P < 0.001), tumour position in the rectum (P < 0.001) and the circumferential location of the tumour (P < 0.001). A T4 tumour was the factor most likely associated with a recommendation against surgery alone (OR 335.96) or SC (OR 61.73). Conclusions: This study shows that clinical factors exert the greatest influence on surgeon decision making, which follows a "fast and frugal" heuristic decision making model. Highlights: Long course neoadjuvant radiotherapy was the treatment of choice in 73% of scenarios. Therapy is decided by tumour stage, position, circumferential location and nodal status. Surgeons used a 'fast and frugal' heuristic model when making these decisions.